6-Axis Hybrid Sensing and Estimation of Tip Forces/Torques on a Hyper-Redundant Robotic Surgical Instrument - (:unkn) unknown (IEEE, 2019)
In this paper a hybrid method for estimation of 6 degree-of-freedom (DOF) laparoscopic instrument tip force/torques in robotic-assisted minimally invasive surgery systems is proposed. The method is implemented on an in-house developed hyper-redundant (11-DOF) surgical robotic forceps prototype. This surgical robot is composed of two modules with a 7-DOF Kuka IIWA manipulator for performing 4-DOF Remote Centre of Motion (RCM) about the trocar and an articulated 4-DOF parallel wrist/gripper mechanism attached to the distal end of the Kuka robot for intra-corporeal manipulation. The hybrid sensor-based/sensorless method fuses torque estimates from the parallel wrist mechanism with measurements from a force sensor attached between the wrist base and the Kuka tool frame. With this approach it is possible to obtain force/torque estimates on all Cartesian axes (x, y, z, yaw, pitch, roll) of the forceps tip. The prototype is one of the first systems designed for robotic surgery that can achieve accurate force estimation on all 6 axes of the instrument tip. Experiment validation results with a force sensor verify the efficacy of the proposed method.